Selective Detection of Misfolded Tau From Postmortem Alzheimer’s Disease Brains - Wu, Ling; Wang, Zerui; Lad, Shradha; Gilyazova, Nailya; Dougharty, Darren T.; Marcus, Madeleine; Henderson, Frances; Ray, W. Keith; Siedlak, Sandra; Li, Jianyong; Helm, Richard F.; Zhu, Xiongwei; et al. (Frontiers in Aging Neuroscience, 2022)
Tau aggregates are present in multiple neurodegenerative diseases known as “tauopathies”, including Alzheimer’s disease, Pick’s disease, progressive supranuclear palsy, and corticobasal degeneration. Such misfolded tau aggregates are therefore potential sources for selective detection and biomarker discovery. Six human tau isoforms in brain tissues and both 3R and 4R isoforms have been observed in the neuronal inclusions. To develop selective markers for AD and related rare tauopathies, we first used an engineered tau protein fragment 4RCF as the substrate for ultrasensitive real-time quaking-induced conversion analyses (RT-QuIC). We showed that misfolded tau from diseased AD and other tauopathy brains were able to seed recombinant 4RCF substrate. We further expanded to use six individual recombinant tau isoforms as substrates to amplify misfolded tau seeds from AD brains. We demonstrated, for the first time to our knowledge, that misfolded tau from the post-mortem AD brain tissues was able to specifically seed all six full-length human tau isoforms. Our results demonstrated that RT-QuIC analysis can discriminate AD and other tauopathies from non-AD normal controls. We further uncovered that 3R-tau isoforms displayed significantly faster aggregation kinetics than their 4R-tau counterparts under conditions of both no seeding and seeding with AD brain homogenates. In summary, our work offers potential new avenues of misfolded tau detection as potential biomarkers for diagnosis of AD and related tauopathies and provides new insights into isoform-specific human tau aggregation.